Changes in facial electromyographic activity in spider-phobic girls after psychotherapy - Leutgeb, Verena (Pergamon Press, 2012)
Recent studies of spider phobia have indicated that disgust is a crucial disorder-relevant emotion and that the facial electromyogram (EMG) of the levator labii region is a reliable disgust indicator. The present investigation focused on EMG effects of psychotherapy in thirty girls (aged between 8 and 14 years) suffering from spider phobia. They were presented with phobia-relevant, generally fear-inducing, disgust-inducing and affectively neutral pictures in a first EMG session. Subsequently, patients were randomly assigned to either a therapy group or a waiting-list group. Therapy-group participants received a single session of exposure therapy in vivo. One week later a second EMG session was conducted. Patients of the waiting-list group received exposure therapy after the second EMG session. After therapy, the girls were able to hold a living spider in their hands and rated spiders more positive, and less arousing, fear- and disgust-inducing. Moreover, they showed a reduction of average levator labii activity in response to pictures of spiders, reflecting the reduction of feelings of disgust. A positive side effect of the therapy was a significant drop in overall disgust proneness and a decreased average activity of the levator labii muscle in response to generally disgust-inducing pictures. Results emphasize the role of disgust feelings in spider-phobic children and suggest that overall disgust proneness should also be targeted in therapy.